Early postoperative liver function parameters as predictors of post-hepatectomy liver failure - Abdelhadi, Schaima; El-Ahmar, Mohamad; Vedder, Katharina; Halawa, Mahmoud; Orth, Vanessa; Hermann, Maike; Mönnichs, Meik; Vassilev, Georgi; Reißfelder, Christoph; Şandra-Petrescu, Flavius Ionuţ (Frontiers in Surgery, 2025)
BackgroundPost-hepatectomy liver failure (PHLF) is a serious complication after liver resection and is associated with increased morbidity and mortality. The current International Study Group of Liver Surgery (ISGLS) definition relies on laboratory values from postoperative day (POD) 5 onwards, which may potentially delay diagnosis and intervention. This study aimed to evaluate whether early postoperative liver function parameters can predict the development of PHLF.MethodsAll patients who underwent elective liver resection between April 2019 and May 2023 were included in the study. Exclusion criteria were emergency or multivisceral resections and incomplete laboratory data. Bilirubin, international normalized ratio (INR), aspartate aminotransferase (AST), and alanine aminotransferase (ALT) were measured on POD 1, 3, and 5. Univariate and multivariate logistic regression analyses were performed to identify independent predictors of PHLF. Receiver operating characteristic (ROC) analysis was performed, and optimal cutoffs on POD3 were determined using the Youden index.ResultsOut of 445 included patients, 38 (8.5%) developed PHLF. Bilirubin, INR, AST, and ALT levels were significantly higher in patients with PHLF from POD 1 onwards. On POD 3, bilirubin ≥1.8 mg/dl (AUC 0.79; sensitivity 93.3%, specificity 62.4%), INR ≥ 1.18 (AUC 0.83; sensitivity 80.6%, specificity 68.8%), AST ≥ 179 U/L (AUC 0.75; sensitivity 68.4%, specificity 74.9%), and ALT ≥ 258 U/L (AUC 0.70; sensitivity 68.8%, specificity 69.8%) demonstrated predictive value. In multivariate analysis, major hepatectomy, bilirubin on POD 3, INR on POD 3, and persistently elevated AST and ALT were confirmed as independent predictors of PHLF.ConclusionBilirubin and INR on POD 3 were the strongest independent predictors of PHLF. Elevated AST and ALT on POD 3 were also valuable prognostic indicators. Relying solely on ISGLS criteria from POD 5 onward may therefore delay diagnosis and intervention. Persistently elevated transaminases should be acknowledged as early indicators of liver dysfunction and considered in future revisions of PHLF definitions.